IMPACT AND COMPARISON OF PREGNANCY INDUCED HYPERTENSION AND OBESITY ON FETAL AND MATERNAL OUTCOME - Umbreen Akram (Army Medical College Rawalpindi, 2019)
Objective: To study the Impact and Comparison of Pregnancy Induced Hypertension and Obesity on Fetal and Maternal Outcome in our set up.